2012
DOI: 10.5005/jp-journals-10017-1016
|View full text |Cite
|
Sign up to set email alerts
|

Free Vascularized Fibular Grafting Preserves Athletic Activity Level in Patients with Osteonecrosis

Abstract: Background: Athletic patients with osteonecrosis of the femoral head have few desirable therapeutic options that preserve athletic ability. A total hip arthroplasty for this young and active patient population would be catastrophic for patients' chances of returning to vigorous athletic endeavors. Therefore, other therapeutic alternatives must be considered prior to enlisting this patient population for a total hip arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…The surgical management of ONFHN is complex and must be tailored to individual patients. For young patients with early disease (before collapse) and without joint-space narrowing, FVFG has been shown to be a cost-effective option [31] allowing return to high activity levels [32] and remains an appropriate treatment option available to patients. However, for many of these patients, FVFG is not a cure, and they will ultimately have progression of their disease, requiring conversion to THA.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical management of ONFHN is complex and must be tailored to individual patients. For young patients with early disease (before collapse) and without joint-space narrowing, FVFG has been shown to be a cost-effective option [31] allowing return to high activity levels [32] and remains an appropriate treatment option available to patients. However, for many of these patients, FVFG is not a cure, and they will ultimately have progression of their disease, requiring conversion to THA.…”
Section: Discussionmentioning
confidence: 99%
“…B. dem Lunatum (Morbus Kienböck), Skaphoid (Morbus Preiser), Femurkopf und Talus. Als mögliche vaskula risierte Knochengrafts kommen gestielte Späne vom distalen Radius, freie mikrovaskuläre Grafts von der medialen Femurkondyle und freie vaskularisierte Fibulae sowie Beckenkämme in Frage [24][25][26][27][28][29][30]. Chirurgische Angiogenese mittels Knochengraft oder Periosttransplantat kommt auch in der Behandlung von Pseudarthrosen des Skaphoids [26,27], der Klavikula, des Humerus, der Unterarmknochen und der Tibia zur Anwendung [31][32][33][34].…”
Section: Behandlungsoptionen ▼unclassified
“…1,9,17,21,23,24,32,34,41,43,[47][48][49][50] Although the pathogenesis is poorly understood overall, there are a variety of direct risk factors that include trauma, radiation, sickle cell disease, caisson disease, and myeloproliferative disorders. 3,4,10,11,23,28,33,43,51 Indirect risk factors include alcohol abuse, chronic corticosteroids, coagulation disorders, statins, human immunodeficiency virus, systemic lupus erythematosus, and pregnancy. 3,4,10,11,23,28,33,43,51 Currently, no single treatment has been identified that undisputedly prevents the progression of the disease.…”
mentioning
confidence: 99%
“…3,4,10,11,23,28,33,43,51 Indirect risk factors include alcohol abuse, chronic corticosteroids, coagulation disorders, statins, human immunodeficiency virus, systemic lupus erythematosus, and pregnancy. 3,4,10,11,23,28,33,43,51 Currently, no single treatment has been identified that undisputedly prevents the progression of the disease. This fact only emphasizes the crucial debate regarding the most optimal treatment algorithm for ONFHN especially in the younger population.…”
mentioning
confidence: 99%
See 1 more Smart Citation